2013
DOI: 10.1007/s10653-013-9582-3
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal concentrations of lead in outdoor and indoor dust and blood of children in Riyadh, Saudi Arabia

Abstract: Because detrimental effects of exposure to lead (Pb) on human health have been observed, we previously investigated concentrations of Pb in water supplies and blood of adult residents of Riyadh, Saudi Arabia. The objectives of the present study were to: (1) examine seasonal rates of deposition of Pb in dust in several areas of Riyadh city, (2) measure concentrations of Pb in both outdoor and indoor dust, (3) compare concentrations of Pb in dust in Riyadh with those reported for other cities, and (4) quantify P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…In West Niger, Goossens and Rajot [34] used and tested seven different theoretical and experimental techniques. ElDesoky et al [16] and Modaihsh and Mahjou [17] collected the dust by using a marble dust collector. Malakootian et al [18] used the British standard method for collecting dust samples.…”
Section: Dust Accumulation Predictionmentioning
confidence: 99%
See 1 more Smart Citation
“…In West Niger, Goossens and Rajot [34] used and tested seven different theoretical and experimental techniques. ElDesoky et al [16] and Modaihsh and Mahjou [17] collected the dust by using a marble dust collector. Malakootian et al [18] used the British standard method for collecting dust samples.…”
Section: Dust Accumulation Predictionmentioning
confidence: 99%
“…Dust flux has been measured and modeled for different applications such as human health impact, air quality, soil formation, and transportation visibility. Several experimental studies have measured dust deposition rates as an average over fairly short time periods in areas such as North Africa, America, the Middle East, and Asia [16][17][18][19][20][21][22][23]. Additionally, dust atmospheric models have been designed to predict dust emission, concentration and deposition [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…The possibility of the circulating lead binding with erythrocytes is high, leading to its rapid distribution throughout the body, including in organs such as the liver and brain, and in the bones [ 6 ]. In addition, the presence of lead in the human body causes oxidative stress through reactive oxygen species production as well as reducing antioxidant defenses’ ability such as by affecting superoxide dismutase and catalase enzymes [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. Therefore, the accurate determination of lead is an important issue in analytical chemistry because of the very low concentrations in some samples as well as the presence of a matrix in real samples, which may interfere with instrumental determination [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hypertension and cardiovascular disease can subsequent develop via Pb‐induced arteriosclerosis, atherosclerosis, and thrombosis [Vaziri, ]. Research on exposed children, the most susceptible group, has also indicated that one's blood lead level (BLL) is more closely associated with the characteristics of one's immediate environment than with the characteristics of a larger area [Kaplowitz et al, ; Morrison et al, ; El‐Desoky et al, ]. Ambient air Pb concentrations have declined over the past 30 years [Richmond‐Bryant et al, ]; predicted BLL in children has been lower in more recent years [Handler and Brabander, ; Li et al, ]; and, in the elderly, the National Health and Nutrition Examination Survey (NHANES) and BLL screening data suggest that elevated BLLs in this population are rare [Vearrier and Greenberg, ].…”
Section: Introductionmentioning
confidence: 99%